KETERLIBATAN STAKEHOLDERS SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Agustian, Rizky; Amiruddin, Amiruddin; Isman, Muhammad (Universitas Islam Negeri Sumatera Utara Medan, 2024)
Research aims to determine the involvement of school stakeholders in improving the quality of education, the efforts of school stakeholders in improving the quality of education and the supporting and inhibiting factors for school stakeholders in improving the quality of education at Bina Taruna 1 Private Vocational School, Medan. This research uses qualitative research with a case study approach. The results of this research show that the involvement of school stakeholders has a significant impact on improving the quality of education in the form of collaborative cooperation, open communication and active participation. The efforts made by school stakeholders in improving the quality of education at Bina Taruna 1 Medan Private Vocational School are only based on six quality standards, namely content standards, process standards, graduation standards, teaching and education staff standards, facilities and infrastructure standards, assessment standards that are classified as good or have met. The supporting factors include effective communication, collaboration, availability of resources and strong support from school leaders. Meanwhile, inhibiting factors include lack of resources, conflict between school stakeholders, lack of motivation and resistance to change. For this reason, it is hoped that stakeholders will jointly develop a clear educational vision and carry out measurable implementation strategies to improve the quality of education at Bina Taruna 1 Medan Private Vocational School.